Transformational Leadership and Organizational Innovation with Mediation and Moderation Variables: A Systematic Literature Review - Ardhana, Rifky; Saputra, Kisno (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to explore the mediating and moderating variables in the relationship between transformational leadership and organizational innovation and also to see the possibility of future research development. Based on a systematic literature review, researchers conducted a content analysis of 21 journals from the Scopus database which were published starting in 2017. The results of the study found 22 mediating variables and 10 moderating variables on the effect of transformational leadership on organizational innovation. The mediation and moderating variables can be applied to the effect of transformational leadership on organizational innovation in various types of organizations so that it is expected to further foster organizational innovation of employees or members of the organization. This study specifically synthesizes various journal articles to look at mediating and moderating variables on the effect of digital leadership on organizational innovation.